Analisis Komparatif Return Saham dan Dampak Faktor Makroekonomi Sebelum dan Selama Covid-19 Antara Perusahaan Pertambangan Syariah dan Konvensional di Bursa Efek Indonesia - Fania Naurah Azizah; Muhamad Umar Mai; Tjetjep Djuwarsa (Journal of Applied Islamic Economics and Finance, 2022)
The purpose of this study was to compare the stock returns of sharia and conventional mining companies before and during the covid-19 pandemic and to determine and analyze the effect of macroeconomic conditions on the stock returns of sharia and conventional mining companies before and during the covid-19 pandemic. The population of this study is the mining sector companies listed on the Indonesia Stock Exchange and included in the main listing board. The sample data was determined by purposive sampling method and resulted in a sample of 16 companies. Secondary data used in this study are stock prices, inflation, rupiah exchange rate, and foreign exchange reserves. The analytical methods used include Mann-Whitney U using SPSS 20 and path analysis using WarpPLS 7.0. The results that can be obtained from this study are that the stock returns of sharia and conventional mining companies both before and during covid did not show any significant differences. Furthermore, in the period before the covid-19 pandemic, inflation had a significant negative effect on Islamic stock returns, while positive and insignificant on conventional stock returns; the rupiah exchange rate has a negative and significant effect on the returns of the two groups of shares; and foreign exchange reserves have a significant negative effect on Islamic stock returns and insignificant negative on conventional stock returns. Meanwhile, during the covid-19 pandemic, inflation had a significant negative effect on stock returns of the two groups; the rupiah exchange rate has a significant negative effect on conventional stock returns and insignificant negative on sharia stock returns; then foreign exchange reserves have a significant negative effect on conventional stock returns and insignificant negative on Islamic stock returns.